Countering terrorism in South Eastern Europe - Morris, Travis 1973-; Hadji-Janev, Metodi 1976- e editor (NATO science for peace and security series, 2017)
In common with many other parts of the world, the region of South Eastern Europe (SEE) faces a significant terrorist threat. Countering this threat represents a major security challenge for government agencies in the region and their partners, and although important counterterrorism advances have been made by NATO nations over the past decade, the complex history, geography, culture, socio-economic and political dynamics of the area mean that these advances need to be contextualized and modified to suit the regional situation. This book presents the contributions to the NATO Advanced Training Course (ATC) 'Countering Terrorism in South Eastern Europe' held over five days at Lake Ohrid, Macedonia, in February 2016. The conference hosted presenters from 15 different countries, and government representatives from the nations of the Balkan region, including Macedonia, Slovenia, Bosnia and Herzegovina, Montenegro, Albania, Bulgaria, Croatia, and Kosovo. The course consisted of five central priorities: contemporary global terrorist practices, radicalization processes and recruitment techniques; terrorist use of cyberspace; legal aspects of countering terrorism; building resilient societies; with the final priority concentrating on SEE counterterrorism. Presenters discussed a wide range of topics, including radicalization and cyberterrorism, all aimed at countering the real and evolving threat of terrorism in the region